UNEXPECTED ALLIANCES – A FEW REMARKS ON OCCASION OF THE DUTCH TRANSLATION OF SOULEYMANE BACHIR DIAGNE’S “HOW TO PHILOSOPHIZE IN ISLAM?” (article received after being in Kazakhstan) - Van der Zveerde, Evert (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2018)
In the following article, Professor Zwerde follows his research in KazNu and offers several arguments on the significance of translation of the work of famous theologian and philosopher Professor Diagne - “How to philosophize Islam?” -into the Dutch language. The author highlights the importance of a problem raised by Diagne concerning the fact that there is a wide diaspora of Muslims in the Netherlands, which is threatened by difficulties in assimilation into the European society and rising islamophobia. Despite the fact that Holland hosts a wide range of Muslim schools, over 450 mosques, political parties have parliament seats and are involved in governmental institutions, not all Islamic authorities can defend their rights properly. In this aspect, according to the author, the study of Islamic philosophy can help to resolve this problem. Thorough evaluation of the tolerant features of Islam can help the Islamic communities in Europe and display Islam as a a religion of peace on the map of global religions. Key words: Soulemane Bachir Diagne, al-Farabi, Islam, tolerant religion.